Children′s behavior pattern and behavior management techniques used in a structured postgraduate dental program - Sharath A; Rekka P; Muthu M; Prabhu V; Sivakumar N (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2009)
Background : Anxiety and fear remain the primary emotion of a child entering a dental office. Successful pediatric dentistry depends not only on the dentist′s technical skills, but also on his ability to acquire and maintain a child′s cooperation. Methods: A retrospective study was done using the case records of 247 children, to evaluate their behavior patterns, based on the Wright′s modification of Frankl′s behavior rating scale. Various behavior management techniques like the tell-show-do, reinforcements, voice control, and hand over mouth exercise used in the postgraduate section of the Department of Pediatric Dentistry, Meenakshi Ammal Dental College, Chennai, India, were also evaluated in this study. Results: Behavior of the children improved on the subsequent visits. Tell-show-do was the most common behavior management technique used and more aversive management techniques were rarely used in managing children in the dental office. Conclusion: Proper assessment of children′s behavior helps the dentist to plan appointments and render effective and efficient dental treatment. Appropriate use of management techniques can improve the child′s behavior in subsequent dental visits.